The Implementation of Pentavalent Vaccine DTaP/IPV/Hib within National Immunization Schedule - Irina V. Mikheeva; Yuliya I. Akimova; Marina A. Mikheeva (Педиатрическая фармакология)
Background. As has been demonstrated by Russian and foreign experience the implementation of combined vaccines within national immunization schedule (NIS) reduces the overall number of injections, enhances vaccination commitment, and as consequence leads to higher vaccination coverage.Objective.Pharmacoeconomic analysis of planned immunization of children aged from 3 to 18 months with combined diphtheria, pertussis, tetanus, poliomyelitis, haemophilus influenza b vaccine (DTaP/IPV/Hib) within Russian Federation NIS.Methods. Modelling; estimation economic method: cost analysis, budget impact analysis. Results. Only health system costs on four planned pentavalent vaccines requires application of 1 013 955 985 roubles. From the government and society perspective the change-over to combined vaccine allows to retrench 1 825 385 700 roubles for children aged from 3 to 18 months for all horizon period.Conclusion. According to budget impact analysis such change-over with controlling only health system costs will require extra expenses. According to government and society perspective (that means social and other expenditures not covered with health system budget) the implementation of scheme of 4-time combined vaccine injections for all cohort allows to reduce cost loading related to infectious disease burden. Present analysis indicated the advisability of pentavalent vaccine implementation for all children within Russian national immunization schedule.